The pirates next door : starring the Jolley-Rogers - Duddle, Jonny (Templar Books, 2012)
When a pirate family moves into her quiet seaside town during ship repairs, young Matilda defies the edicts of the gossiping adults in the community to befriend young pirate Jim Lad.